Mengembangkan kompetensi guru Sejarah SMK yang inovatif melalui pelatihan videografi - Sulistyo, Wahyu Djoko; Utami, Indah Wahyu Puji; Widiadi, Aditya Nugroho; Umami, Riza Oktavia; Ismail, Akhmat Safiudin (Jurnal Praksis dan Dedikasi Sosial, 2025)
Enhancing the innovative competencies of vocational high school history teachers through videography training This videography training was conducted to train history teachers at vocational schools throughout the Malang Regency to be able to develop innovative history learning media in the form of videography. One of the indicators of an innovative teacher is being able to develop their own learning media according to the needs and characteristics of students in the class. A common problem in learning history in vocational schools is that students are less interested in history lessons because they are boring and not a subject that is appropriate for their field. One of the causes of student boredom is the lack of creativity and innovation of teachers in using learning media. So, it is necessary to conduct training to improve teacher competence in developing innovative learning media, namely videography. This training is realized in three stages, namely pre-activities, core activities and post-activities. The implementation of this history videography training was carried out for two days, namely on July 23, 2024, online using Zoom software and on July 25, 2024, offline at the Museology Laboratory, Department of History, State University of Malang. The results of the training, firstly showed that history teachers of vocational schools throughout Malang Regency assessed that the videography training succeeded in improving their competence with the results of the evaluation questionnaire of 80-93 percent, secondly the output of the videography project was able to be completed by the participants so that it can be used as an innovative learning media. With this training, it is hoped that history educators will not only teach but can also develop historical videos that can be used as a medium for learning history in the classroom. Pelatihan videografi ini dilakukan untuk melatih guru-guru sejarah SMK se-Kabupaten Malang agar dapat mengembangkan media pembelajaran sejarah yang inovatif dalam bentuk videografi. Karena salah satu indikator guru yang inovatif yaitu mampu mengembangkan sendiri media pembelajaranya sesuai dengan kebutuhan dan karakteristik peserta didik di kelas. Problematika umum dalam pembelajaran sejarah di SMK adalah siswa kurang tertarik dengan pelajaran sejarah karena membosankan dan bukan sebagai mata pelajaran yang sesuai di bidang mereka. Salah satu penyebab kebosanan siswa karena kurang kreatif dan inovatifnya guru dalam penggunaan media pembelajaran. Sehingga perlu dilakukan pelatihan untuk meningkatkan kompetensi Guru dalam mengembangkan media pembelajaran yang inovatif, yaitu videografi. Pelatihan ini direalisasikan dengan tiga tahap yakni pra kegiatan, kegiatan inti dan pasca kegiatan. Pelaksanaan pelatihan videografi sejarah ini dilaksanakan selama dua hari yakni pada 23 Juli 2024 secara daring menggunakan software Zoom dan pada 25 Juli 2024 secara luring di Laboratorium Museologi Departemen Sejarah, Universitas Negeri Malang. Hasil pelatihan, yang pertama menunjukkan bahwa para guru sejarah SMK se-Kabupaten Malang menilai pelatihan videografi berhasil meningkatkan kompetensinya dengan hasil angket evaluasi 80-93 persen, kedua ouput project videografi mampu diselesaikan oleh para peserta sehingga dapat dijadikan media pembelajaran yang inovatif. Dengan pelatihan ini diharapkan para pendidik sejarah tidak hanya sekadar mengajar saja, melainkan dapat mengembangkan video sejarah yang dapat digunakan untuk media pembelajaran sejarah di kelas.